b - 9 (b, 2007)
Articles on the history from 1858 to 1947, of Mitford Hospital and of Dhaka Medical School, both located in Dhaka, Bangladesh.
Includes bibliographical references (p. [467]-472) and index.
In Bengali; includes passages in English.
Keywords: Mitford Hospital (Dhaka, Bangladesh) -- History; Dhaka Medical School -- History; Hospitals -- Bangladesh -- Dhaka -- History; Medical colleges -- Bangladesh -- Dhaka -- History